2022
DOI: 10.3390/ijerph19063746
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Risk Assessment of Second- and Third-Hand Tobacco Smoke Using Urinary Cotinine Levels in South Korea

Abstract: Exposure to environmental tobacco smoke (ETS) is the reason for approximately 1% of global mortality. ETS exposure can happen either as inhalation of direct cigarette smoke (second-hand smoke) or its associated residue particles (third-hand smoke), especially when living with a smoker in the same family. This study investigated the association between the urinary cotinine levels, as biomarkers of exposure to tobacco smoke, of smokers and those exposed to second-hand and third-hand smoke while living in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Several studies have shown that corrected urine cotinine levels are a better representation of serum cotinine levels. 10,18) Conversely, in another study, uncorrected values showed a stronger correlation with serum cotinine levels than corrected values. 19) In the present study, cor- In a Western study on secondhand smoke, SBP elevation was associated with increased serum cotinine among those in contact with secondhand smok, 20) and preschool children with smoking parents had significantly higher SBP and DBP.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Several studies have shown that corrected urine cotinine levels are a better representation of serum cotinine levels. 10,18) Conversely, in another study, uncorrected values showed a stronger correlation with serum cotinine levels than corrected values. 19) In the present study, cor- In a Western study on secondhand smoke, SBP elevation was associated with increased serum cotinine among those in contact with secondhand smok, 20) and preschool children with smoking parents had significantly higher SBP and DBP.…”
Section: Discussionmentioning
confidence: 84%
“…From this group, current self-reported non-smokers, verified by measuring urine cotinine levels, who did not use any cigarettes, e-cigarettes, nicotine replacement products, or other types of cigarettes, were included (n=9,328). Urine cotinineverified non-smokers were defined as those with a urine cotinine-tocreatinine ratio ≤100 μg/g [ 10 ]. After excluding participants with missing values, 9,273 participants were included in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SHS exposure among people living with a combustion cigarette smoker is currently a popular topic [17][18][19]. However, assessments of SHS exposure due to HTP use are scarce.…”
Section: Introductionmentioning
confidence: 99%